FOOD, MICROBES, AND THE MIND: INTERVENTIONS AND TECH-FOR-HEALTH IMPLICATIONS - Wojciech Pabis; Patryk Biesaga; Konrad Kotte; Olaf Jadanowski; Kamil Łebek; Weronika Sobota; Przemysław Piskorz; Daria Litworska-Sójka; Bartosz Komsta; Julia Lipiec (International Journal of Innovative Technologies in Social Science, 2025)
Research objectives: To synthesise recent evidence on microbiome-brain relationships across Alzheimer’s disease, Parkinson’s disease, multiple sclerosis, autism spectrum disorder, depression and schizophrenia; to summarise therapeutic strategies (diet, probiotics/prebiotics, psychobiotics, faecal microbiota transplantation) and biological mechanisms; and to outline translational considerations relevant to technology and society.Methods: Structured narrative review with a PRISMA-style workflow.Sources: PubMed/MEDLINE and Web of Science (Core Collection), plus handsearch/citation chasing (English/Polish; 1 Jan 2013–31 Mar 2025). Ten authors performed duplicate screening and data charting. Heterogeneity precluded meta-analysis. Included n=21 studies after databases identified n=1,500 records, duplicates n=540, screened n=960, and full texts assessed n=252 (databases) and n=48 from other sources; the reference list also cites background/methodological works not counted in PRISMA.Key findings: Across conditions, a consistent signal is loss of short-chain-fatty-acid (SCFA)–producing taxa, increased intestinal permeability and immune activation. High-fibre/polyphenol diets and multi-strain probiotics/prebiotics show theclearest-though modest-improvements in inflammatory markers and selected mood/quality-of-life outcomes; cognitive effects are mixed. Psychobiotics show preliminary benefits; faecal microbiota transplantation remains experimental in neurology. Mechanistic strands include SCFAs, tryptophan/kynurenine metabolism, vagal signalling and HPA-axis modulation.Conclusions: The gut microbiome is a modifiable contributor to brain health. Low-risk dietary optimisation is warranted, and probiotic use should be strain-specific. Priorities include adequately powered, preregistered trials with harmonised microbiome pipelines and mechanistic endpoints, plus evaluation of precision-nutrition and data-driven decision support under robust privacy governance.